Street Vending Management According to The Policy of Bangkok. - Woraphatthirakul, Paphatsorn (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The research paper aimed to: 1) study the current problems on street vending in Bangkok: 2) study the policy of street vending management in Bangkok: and 3) to recommend problems, obstacles and solutions to the occupational situation of street vendors, as well as policies or measures for the street vending management in Bangkok. The qualitative research method was conducted by in-depth interviews from a group of 25 key informants. The research instruments were interview questionnaires and analysis, reading results, interpreting and conclusions by analyzing qualitative data revealed instead of the facts as follow: 1. From the current problems in the street vending management in Bangkok, the socio-economic situation is a reflection of the traditional way of life in street vending. The products sold represent the cultural and urban way of the informal economy, which are the drivers for distribution in the community to the current street vending career. 2. The policy of street vending in Bangkok in term of the policy of Act on the Maintenance of the Cleanliness and Orderliness of the Country, B.E. 2535, which is clear to cover the implementation of the policy and suitable for the area conditions but there are limitations on the number of staff and insufficient budgets, which have not been achieved by many factors. 3. Based on research findings are as follow: 3.1) Establish a policy to promote and support the career development of street vendors, such as investment lending, other career advancement with higher income and security in order to permanently reduce the number of street vendors. 3.2) Use control methods in terms of the number of street vendors and the controls on the area permitted to trade, and to promote orderliness and hygiene in the areas permitted for trade. 3.3) Coordinated cooperation of street venders and residents held a meeting to educate traders to adjust the attitude of policy implementation was a satisfying achievement. 3.4) Tackling problems that cause poverty and increasing development opportunities for people and rural areas, both at the macro and micro level, which can be a permanent solution to the street vending problems. Article history: Received 16 June 2020 Revised 28 October 2020 Accepted 2 November 2020 SIMILARITY INDEX = 0.00 %